Parametrial hydatid cyst with cystovesical fistula: a rare presentation - Shukla, Samir; Khare, Vidhu S.; Koshariya, Mahim; Lal, Vikas; Parmar, Bhupendra; Tiwari, Shashikant; Songra, M. C. (International Surgery Journal, 2019)
Hydatid disease is a parasitic infestation by a tapeworm of the genus Echinococcus. Theoretically, echinococcosis can involve any organ. The liver is the most common organ involved, followed by the lungs. However, uterus and and adnexa have an incidence of 0.5-1%. Till date, three cases have been reported in which a parametrial hydatid cyst formed a bladder fistula. A 57 year old female was admitted with complaint of burning micturition along with white coloured urine for the last 15-20 days with no other significant history. On examination and evaluation, it was suspected to a neoplastic pelvic mass causing gross right sided hydronephrosis. All biochemical markers were within normal limits. The patient was explored surgically on which a thick-walled lesion was found in right parametrium. The cavity of the lesion was filled with daughter hydatid cyst, along with communication into the bladder via a fistula. Open cystectomy was done after evacuation of daughter cysts and irrigation with scolicidal agents. The fistula was repaired. The patient recovered uneventfully and was doing well on follow-up. The incidence of hydatid cysts in the female reproductive system is very low and constitutes less than 0.5% of all hydatid cysts. However, rare cases have been reported, thus the clinician must be aware of this rare disease and should take precautions while operating, as any spillage may lead to anaphylactic shock.